1980
DOI: 10.1111/j.1365-2362.1980.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma aspirin esterases in normal individuals, patients with alcoholic liver disease and rheumatoid arthritis: characterization and the importance of the enzymic components

Abstract: Abstract. Two enzymes in human plasma capable of hydrolysing aspirin (‘aspirin esterases’) were isolated (by ion exchange and gel chromatography) and characterized, since their activity has been reported to be important in certain disease/therapeutic situations. The optimum pH and calcium concentration for plasma aspirin esterases were 80 and 5 mmol/1 respectively. The main enzymic activity (enzyme ‘C’) was associated with plasma cholinesterases. This component had a Km of 6‐5 mmol/1 for aspirin and a Kmax of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…The cellular enzyme is probably a 'non specific' esterase whereas the plasma enzyme activity is due to cholinesterase as previously demonstrated by Rainsford et al (1980).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The cellular enzyme is probably a 'non specific' esterase whereas the plasma enzyme activity is due to cholinesterase as previously demonstrated by Rainsford et al (1980).…”
mentioning
confidence: 54%
“…Rainsford et al (1980) have shown that the main plasma aspirin esterase activity is associated with the plasma cholinesterases.…”
mentioning
confidence: 99%
“…Albumin, the most abundant protein in plasma (Theodore, 1996), displays pseudo-enzymatic properties and has been found to catalyze the hydrolysis of numerous compounds, such as cinnamoyl imidazole (Ohta et al, 1983), p-nitrophenyl esters (Means and Bender, 1975;Kurono et al, 1979;Watanabe et al, 2000;Sakurai et al, 2004;Lockridge et al, 2008), olmesartan medoxomil (Ma et al, 2005), carbaryl (Sogorb et al, 2004), aspirin (Rainsford et al, 1980;Liyasova et al, 2010), organophosphate insecticides (Sultatos et al, 1984), and Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma and liver esterases capable of hydrolysing aspirin have not been purified, Rainsford et al (1980) has separated two components from plasma. One component appears to be similar to plasma cholinesterase, and the other is an aryl esterase.…”
Section: Discussionmentioning
confidence: 99%